The Effect of Technological Parameters on the Formation of Fillet Welds in Two-Electrode Submerged Arc Welding - Sholokhov Mikhail; Buzorina Daria; Melnikov Anton; Fiveyskii Andrey; Mosin Alexey (MATEC Web of Conferences, 2021)
The development of transport infrastructure contributes to an increase in the demand for bridge structures, which leads to the need to increase the productivity of their manufacture. The overall increase in welding productivity is facilitated by an increase in the volume of welds performed in a single pass. It is proposed to use two-electrode welding. Computer analysis of such process has shown that an acceptable fillet weld formation can be ensured by rational parameters of the welding process, including the positioning of the electrodes relative to the weld. The distance between the electrodes should be approximately equal to the required leg size, and the electrodes shall be turned by an angle of 45 ° so that the electrode on the web lags behind the one on the flange, and the axis of this electrode is located at a distance equal to half of the required leg, the tilt angle of the torch should be 30 ° from vertical. With the indicated positioning of the electrodes, an asymmetrical weld pool is formed, the end of which is strongly displaced to the web. The melt runoff from the web to the flange is limited by the lower boundary of the weld pool, consequently, the finishing of the runoff and solidification of the metal is shifted towards the web. This fact improves the formation of weld surface, reducing the meniscus at the web and the influx on the flange. Thus, the decrease of the meniscus at the web and the influx on the flange when the arc is placed on the web can be explained by the asymmetric process of metal solidification, which proceeds predominantly from the flange to the web.